Preparation method of InO-based finger-like structure photocatalyst
By preparing the In2O3-based ring-shaped configuration photocatalyst and supporting iridium atoms on its surface, the problem of insufficient photocatalytic conversion efficiency and stability of traditional In2O3 photocatalysts is solved, and efficient photocatalytic performance is achieved.
Patent Information
- Application Number
- CN202411714613.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-21
AI Technical Summary
Traditional In2O3 photocatalysts have problems such as high photogenerated electron-hole recombination rate and narrow light absorption range, which limits their practical application.
Using a preparation method of In2O3-based ring-shaped configuration photocatalyst, by adding indium source, terephthalic acid and N,N-dimethylformamide to the reactor, performing oil bath heating and calcining heating reactions, forming an In2O3 catalyst with ring-shaped configuration, and supporting iridium atoms on its surface, enhancing catalytic activity through deposition reduction reaction.
By forming a ring-like configuration and supporting iridium atoms, the specific surface area, active site density and charge separation efficiency of the photocatalyst are significantly improved, and the photocatalytic conversion efficiency and stability are improved.
Smart Images

Figure CN119657129A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation, and in particular to a method for preparing an In2O3-based wrench-shaped photocatalyst. Background Art
[0002] In recent years, photocatalytic technology has shown great potential in the field of environmental purification and green synthesis. Among them, the development of efficient and stable photocatalysts has become a research hotspot. Oxide semiconductors, especially indium trioxide (In2O3), are considered to be ideal photocatalytic material candidates due to their wide bandgap and good chemical stability. However, traditional In2O3 has problems such as high recombination rate of photogenerated electrons and holes and narrow light absorption range, which limits its practical application.
[0003] In order to overcome the above difficulties, researchers are committed to developing new configurations and modification strategies. At present, although there are some In2O3-based photocatalysts on the market, they generally have problems such as complex synthesis process, high cost, and unstable performance. Therefore, it is urgent to explore a simple and economical preparation method to improve the comprehensive performance of In2O3 photocatalysts and meet the growing needs of environmental governance and chemical synthesis. To this end, the present invention proposes a preparation method of In2O3-based finger-shaped configuration photocatalyst. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing an In2O3-based wrench-shaped photocatalyst to solve the limitations of the In2O3 photocatalyst in the prior art in terms of photocatalytic conversion efficiency, stability, etc.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing an In2O3-based finger-shaped photocatalyst, comprising the following steps:
[0006] Step 1, adding a certain amount of indium source and terephthalic acid into a reactor, and then adding N,N-dimethylformamide (DMF) and stirring to dissolve all the solids to obtain solution A;
[0007] Step 2, placing the solution A obtained in step 1 in an oil bath pot for heating, cooling and filtering after the reaction is completed, washing and drying to obtain a solid powder;
[0008] Step 3, calcining and heating the solid powder dried in step 2 to obtain an In2O3 catalyst with a wrench-shaped configuration;
[0009] Step 4, adding iridium ion reagent to the In2O3 catalyst with a wrench-shaped configuration obtained in step 3, adding an appropriate amount of deionized water and stirring;
[0010] Step 5, adding sodium borohydride solution dropwise to the product obtained in step 4 while stirring, carrying out deposition reduction reaction at room temperature for 1-3 hours, filtering and collecting, washing with anhydrous ethanol and deionized water for 3-5 times each, and vacuum drying at 80°C for 12 hours to obtain a wrench-shaped In2O3 photocatalyst loaded with iridium atoms.
[0011] As a preferred technical solution of the present invention, in step 2, the oil bath heating temperature is 120-160° C., and the heating time is 10-60 min.
[0012] As a preferred technical solution of the present invention, in step 3, the heating temperature of the calcination heating reaction is 300-400°C, and the reaction time is 3-4h.
[0013] As a preferred technical solution of the present invention, the iridium ion reagent is iridium chloride or sodium hexachloroiridate.
[0014] As a preferred technical solution of the present invention, the iridium chloride is iridium trichloride and its hydrate.
[0015] As a preferred technical solution of the present invention, the sodium hexachloroiridate is sodium hexachloroiridate (III) and its hydrate.
[0016] As a preferred technical solution of the present invention, in step 5, the deposition reduction reaction is carried out for 2 hours, and the amount of deposition is 0.3-0.7 wt%.
[0017] As a preferred technical solution of the present invention, the deposition amount is 0.5 wt %.
[0018] As a preferred technical solution of the present invention, the indium source is indium nitrate.
[0019] The present invention also proposes the use of an In2O3-based wrench-shaped photocatalyst in a photocatalytic γ-lactam reaction, wherein the amount of the photocatalyst added is 0.05-0.1 mol%.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention discloses a method for preparing an In2O3-based finger-shaped photocatalyst. The In2O3-based finger-shaped photocatalyst particle configuration has an internal hollow finger shape, which increases the specific surface area of the photocatalyst particles, increases a large number of active sites, and enables photocatalytic reactions on both the inner and outer walls. At the same time, sufficient thickness can ensure the mechanical strength of the photocatalyst particles, reduce thermal stress and prevent structural collapse. The supported iridium atoms play a key role in the photocatalyst, acting as an efficient charge transfer medium to significantly promote the separation of photogenerated electrons and holes and reduce recombination losses, and also increase surface active sites, accelerate catalytic reactions, and improve conversion efficiency. At the same time, the addition of iridium atoms optimizes the electronic structure of the catalyst, adjusts the energy level layout, improves light absorption and charge transfer, and comprehensively enhances the photocatalytic performance.
[0022] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope image of the photocatalyst particles described in Example 1 of the present invention.
[0024] Figure 2 This is a transmission electron microscope image of the photocatalyst particles described in Example 11 of the present invention, wherein the red circles represent iridium metal atoms.
[0025] Figure 3 This is a photocatalytic γ-lactam reaction activity diagram of the photocatalyst particles described in Example 11 of the present invention.
[0026] Figure 4 This is a diagram showing the activity of the photocatalytic decomposition of water to produce hydrogen by the photocatalyst particles described in Example 11 of the present invention.
[0027] Figure 5 This is a graph of the ultraviolet-visible diffuse reflection absorption spectrum of the catalyst carrier and photocatalyst particles described in Example 1 of the present invention.
[0028] Figure 6 This is the photocurrent (it) diagram of the catalyst carrier described in Example 1 of the present invention.
[0029] Figure 7 This is the EIS graph of the catalyst support described in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] See also Figure 1-7 In this embodiment, a method for preparing an In2O3-based wrench-shaped photocatalyst is provided, comprising the following steps:
[0032] Step 1, adding a certain amount of indium source and terephthalic acid into a reactor, and then adding N,N-dimethylformamide (DMF) and stirring to dissolve all the solids to obtain solution A;
[0033] Step 2, placing the solution A obtained in step 1 in an oil bath and heating it at a temperature of 120-160° C. for 10-60 min. After the reaction is completed, cooling, filtering, washing and drying are performed to obtain a solid powder;
[0034] Step 3, calcining and heating the solid powder dried in step 2, wherein the heating temperature of the calcination and heating reaction is 300-400° C. and the reaction time is 3-4 hours to obtain an In2O3 catalyst with a wrench-shaped configuration;
[0035] Step 4, adding an iridium ion reagent to the In2O3 catalyst with a wrench-shaped configuration obtained in step 3, adding an appropriate amount of deionized water and stirring, wherein the iridium ion reagent is iridium chloride or sodium hexachloroiridate, further, the iridium chloride is iridium trichloride and its hydrate, and the sodium hexachloroiridate is sodium hexachloroiridate (III) and its hydrate;
[0036] Step 5, adding sodium borohydride solution dropwise to the product obtained in step 4 while stirring, carrying out a deposition reduction reaction at room temperature for 1-3 hours, filtering and collecting, washing with anhydrous ethanol and deionized water for 3-5 times respectively, and vacuum drying at 80°C for 12 hours to obtain a wrench-shaped In2O3 photocatalyst loaded with iridium atoms; wherein, preferably, the deposition reduction reaction is carried out for 2 hours; the amount of deposition is 0.3-0.7wt%; preferably, the amount of deposition is 0.5wt%.
[0037] The present invention also proposes the use of an In2O3-based wrench-shaped photocatalyst in a photocatalytic γ-lactam reaction, wherein the amount of the photocatalyst added is 0.05-0.1 mol%; preferably, the amount of the photocatalyst added is 0.08 mol%.
[0038] Among them, the unique finger-shaped configuration can increase the specific surface area and light capture capacity of the photocatalyst; the loading of single atoms of precious metals (such as iridium) can significantly improve the charge separation efficiency and enhance the catalytic activity. By loading single atoms of iridium, efficient photocatalytic conversion of target compounds such as γ-lactam can be achieved, which significantly improves the photocatalytic performance and has great scientific significance and application value.
[0039] Among the relatively stable trivalent and tetravalent iridium compounds, the iridium ion reagent uses a trivalent iridium compound with weaker oxidizing property, which is beneficial to its deposition reduction and has less effect on the oxide catalyst carrier with certain reducibility.
[0040] The yield of the photocatalyst-catalyzed γ-lactam reaction can be investigated by the ratio of the product to the reactant. The photocatalytic reaction is carried out in a homemade specially constructed photoreactor. When testing the yield of each catalyst, 100 mg of the catalyst and an appropriate amount of γ-lactam are taken to prepare catalyst solutions of different concentrations. Specific examples 1-3 are catalyst solutions of 0.08 mol%, 0.1 mol%, and 0.05 mol% concentrations, respectively. The reaction is carried out for 8 hours under the same illumination and the same mass of reactants, and the product is analyzed by gas chromatography.
[0041] Table 1 Effect of photocatalytic conditions on the yield of γ-lactam reaction:
[0042] Example Catalyst concentration (mol%) illumination Photocatalytic yield (%) Activity decay (%) Application Example 1 0.08 have 89 5 Application Example 2 0.1 have 86 9 Application Example 3 0.05 have 85 3 Application Comparative Example 1 0 have 0 0 Application Comparative Example 2 0.08 none 0 0
[0043] Example 1
[0044] Dissolve 0.73g of 1,4-benzenedicarboxylic acid and 0.7g of indium nitrate in 160mL of DMF. Then, heat the beaker in an oil bath to 120°C and keep it for 30min. After the reaction is completed, slowly cool the beaker to room temperature and pour out the mixture. Collect the powder by centrifugation, wash it 3 times with anhydrous ethanol or deionized water, and then dry it to obtain the precursor. Finally, calcine the precursor nanobox at 400°C in air for 3h to prepare the indium trioxide catalyst carrier.
[0045] The photocatalytic yield of the photocatalyst particles in this embodiment is 89%, and the activity decay is 5%.
[0046] Example 2
[0047] Dissolve 0.73g of 1,4-benzenedicarboxylic acid and 0.35g of indium nitrate in 160mL of DMF. Then, heat the beaker in an oil bath to 120°C and keep it for 30min. After the reaction is completed, slowly cool the beaker to room temperature and pour out the mixture. Collect the powder by centrifugation, wash it 3 times with anhydrous ethanol or deionized water, and then dry it to obtain the precursor. Finally, calcine the precursor nanobox at 400°C in air for 3h to prepare the indium trioxide catalyst carrier.
[0048] The photocatalytic yield of the photocatalyst particles in this embodiment is 86%, and the activity decay is 9%.
[0049] Example 3
[0050] Dissolve 0.73g of 1,4-benzenedicarboxylic acid and 1.0g of indium nitrate in 160mL of DMF. Then, heat the beaker in an oil bath to 120°C and keep it for 30min. After the reaction is completed, slowly cool the beaker to room temperature and pour out the mixture. Collect the powder by centrifugation, wash it 3 times with anhydrous ethanol or deionized water, and then dry it to obtain the precursor. Finally, calcine the precursor nanobox at 400°C in air for 3h to prepare the indium trioxide catalyst carrier.
[0051] The photocatalytic yield of the photocatalyst particles in this embodiment is 83%, and the activity decay is 3%.
[0052] The difference of Comparative Example 1 is that no catalyst is added to the solution; the difference of Comparative Example 2 is that the catalyst solution is 0.08 mol%, but no light irradiation is performed.
[0053] It can be seen from the experimental results summarized in Table 1 that catalysts and light are essential for the reaction to occur; under the conditions of the embodiments, the yield of the photocatalyst-catalyzed γ-lactam reaction is above 75%, among which Application Example 1 is the best, and the yield of the target molecule can reach 95%.
[0054] Example 4
[0055] Dissolve 0.73g of 1,4-benzenedicarboxylic acid and 0.7g of indium nitrate in 160mL of DMF. Then, heat the beaker in an oil bath to 120°C and keep it for 30min. After the reaction is completed, slowly cool the beaker to room temperature and pour out the mixture. Collect the powder by centrifugation, wash it 3 times with anhydrous ethanol or deionized water, and then dry it to obtain the precursor. Finally, calcine the precursor nanobox at 400°C in air for 3h to prepare the indium trioxide catalyst carrier.
[0056] An appropriate amount of iridium ion reagent was added to the obtained In2O3 catalyst, and an appropriate amount of deionized water was added and stirred, and then sodium borohydride solution was added dropwise while stirring, and the catalyst was subjected to a deposition reduction reaction at room temperature for 2 hours, and the amount of deposition was 0.5wt%. Among them, the iridium ion reagent selected a trivalent iridium compound with weak oxidizing property, which is conducive to its deposition reduction and has little effect on the oxide catalyst carrier with certain reducibility, filtered and collected, washed with anhydrous ethanol and deionized water for 3-5 times respectively, and vacuum dried at 80°C for 12 hours to obtain a wrench-shaped In2O3 photocatalyst 4 loaded with iridium atoms.
[0057] It should be noted that the iridium ion reagent can be iridium chloride or sodium hexachloroiridate. More specifically, iridium chloride is iridium trichloride and its hydrate; sodium hexachloroiridate is sodium hexachloroiridate (III) and its hydrate.
[0058] The photocatalytic yield of the photocatalyst particles in this embodiment is 95%.
[0059] Table 2 Effect of catalyst preparation method on catalytic γ-lactam reaction yield:
[0060]
[0061] Embodiment 5-10
[0062] The synthesis steps of Examples 5-10 are the same as those of Example 4, and the amounts of chemical reagents used in the synthesis and the synthesis conditions are shown in Table 2. Other conditions and the amounts of raw materials remain unchanged. The yield of the photocatalyst-catalyzed γ-lactam reaction of each example is also shown in Table 2.
[0063] According to experimental data, when 0.73g of 1,4-benzenedicarboxylic acid and 0.7g of indium nitrate were selected as raw materials, hydrothermally reacted at 140℃ for 30min, calcined at 400℃ for 3h, and loaded with about 0.5wt% of iridium nanoparticles, the prepared catalyst showed excellent performance, with a catalytic activity of up to 95%. In contrast, even under the same conditions, the rubidium-loaded catalyst can only achieve a catalytic efficiency of 68% to 76%, which is significantly inferior. This fully proves that the photocatalyst particles of the present invention have outstanding catalytic activity and are a breakthrough in the field of photocatalysis.
[0064] Embodiment 11
[0065] Dissolve 0.73g of 1,4-benzenedicarboxylic acid and 0.7g of indium nitrate in 160mL of DMF. Then, heat the beaker in an oil bath to 120°C and keep it for 30min. After the reaction is completed, slowly cool the beaker to room temperature and pour out the mixture. Collect the powder by centrifugation, wash it 3 times with anhydrous ethanol or deionized water, and then dry it to obtain the precursor. Finally, calcine the precursor nanobox at 400°C in air for 3h to prepare the indium trioxide catalyst carrier.
[0066] Add an appropriate amount of iridium ion reagent to the obtained In2O3 catalyst, add an appropriate amount of deionized water and stir, then add sodium borohydride solution dropwise while stirring, and perform deposition reduction reaction at room temperature for 2 hours, and the amount of deposition is 0.5wt%. Among them, the iridium ion reagent uses a trivalent iridium compound with weak oxidizing property, which is conducive to its deposition reduction and has little effect on the oxide catalyst carrier with certain reducibility. Filter and collect, wash with anhydrous ethanol and deionized water for 3-5 times respectively, and vacuum dry at 80°C for 12 hours to obtain a wrench-shaped In2O3 photocatalyst 11 loaded with iridium atoms.
[0067] It should be noted that the iridium ion reagent can be iridium chloride or sodium hexachloroiridate. More specifically, iridium chloride is iridium trichloride and its hydrate; sodium hexachloroiridate is sodium hexachloroiridate (III) and its hydrate.
[0068] Application of photocatalytic water decomposition to produce hydrogen
[0069] In this example, the photocatalyst prepared in Example 11 was used to test the activity of decomposing water to produce hydrogen.
[0070] Specifically, weigh 100 mg of photocatalyst and slowly add it to a photocatalytic reaction container containing 170 mL of water and 30 mL of triethanolamine. Place the reaction container on a magnetic stirrer and adjust the stirring speed so that the photocatalyst is evenly dispersed in the water. The stirring speed is generally controlled at 300 rpm. Place the reaction container containing the photocatalyst and water in a suitable position below the light source. Make sure that the light from the light source can evenly irradiate the reaction solution. Connect the gas collection device to ensure a good seal. Turn on the light source, start timing, and regularly observe the gas generation during the reaction. At the same time, a gas chromatograph can be used to analyze the composition of the generated gas (hydrogen) to determine the efficiency of photocatalytic water decomposition. Through the above-mentioned photocatalytic water decomposition test, it can be obtained that the amount of hydrogen precipitated by the catalyst within 4 hours can reach 2.34 mmol.
[0071] Table 3 Effect of catalyst preparation method on photocatalytic water decomposition hydrogen evolution activity
[0072]
[0073] Examples 12-17
[0074] Examples 12 to 17 follow the same synthesis path as Example 11, and the detailed parameters and catalytic performance are listed in Table 3. The experiment found that when 0.73g of indium salt was used, reacted under hydrothermal conditions at 140°C for 30min, then calcined at 400°C for 3h, and loaded with about 0.5wt% of iridium nanoparticles, the prepared catalyst showed the best performance and could produce 2.34mmol of hydrogen within 4h. In contrast, under the same conditions, similar catalysts can only produce 0.9 to 2.15mmol of hydrogen, which is significantly lower than the optimal example of the present invention. This result strongly proves that the photocatalyst particles described in the present invention have excellent catalytic activity and have brought significant progress in the field of photocatalytic hydrogen evolution.
[0075] Photocatalyst particles optimize fluid dynamics, reduce pressure drop, and improve mass transfer efficiency of reactants and products. The supported iridium atoms not only act as efficient charge transfer media, significantly promote the separation of photogenerated electrons and holes, reduce recombination losses, but also increase surface active sites, accelerate catalytic reactions, and improve conversion efficiency. At the same time, the addition of iridium atoms optimizes the electronic structure of the catalyst, improves light absorption and charge transfer, and comprehensively enhances photocatalytic performance.
[0076] By supporting iridium single atoms on the surface of In2O3, an efficient photocatalytic system is constructed. This method uses solvent thermal synthesis technology to finely control the microstructure of In2O3 to form a unique finger-shaped appearance, and then accurately supports iridium single atoms through wet chemical methods, which significantly improves the density of photocatalytic active sites and the efficiency of electron transfer. The obtained catalyst exhibits excellent photocatalytic conversion of γ-lactam under visible light irradiation, with a conversion rate of more than 95%. The present invention has opened up a new path for the environmentally friendly synthesis of γ-lactam and has broad potential for industrial application.
[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an In2O3-based wrench-shaped photocatalyst, characterized in that: The steps include: Step 1, adding a certain amount of indium source and terephthalic acid into a reactor, and then adding N,N-dimethylformamide (DMF) and stirring to dissolve all the solids to obtain solution A; Step 2, placing the solution A obtained in step 1 in an oil bath pot for heating, cooling and filtering after the reaction is completed, washing and drying to obtain a solid powder; Step 3, calcining and heating the solid powder dried in step 2 to obtain an In2O3 catalyst with a wrench-shaped configuration; Step 4, adding iridium ion reagent to the In2O3 catalyst with a wrench-shaped configuration obtained in step 3, adding an appropriate amount of deionized water and stirring; Step 5, adding sodium borohydride solution dropwise to the product obtained in step 4 while stirring, carrying out deposition reduction reaction at room temperature for 1-3 hours, filtering and collecting, washing with anhydrous ethanol and deionized water for 3-5 times each, and vacuum drying at 80°C for 12 hours to obtain a wrench-shaped In2O3 photocatalyst loaded with iridium atoms.
2. The method for preparing an In2O3-based finger-shaped photocatalyst according to claim 1, characterized in that: In step 2, the oil bath is heated at a temperature of 120-160° C. for a heating time of 10-60 min.
3. The method for preparing an In2O3-based wrench-shaped photocatalyst according to claim 1, characterized in that: In step 3, the heating temperature of the calcination heating reaction is 300-400° C., and the reaction time is 3-4 hours.
4. The method for preparing an In2O3-based wrench-shaped photocatalyst according to claim 1, characterized in that: The iridium ion reagent is iridium chloride or sodium hexachloroiridate.
5. The method for preparing an In2O3-based finger-shaped photocatalyst according to claim 4, characterized in that: The iridium chloride is iridium trichloride and its hydrate.
6. The method for preparing an In2O3-based wrench-shaped photocatalyst according to claim 1, characterized in that: The sodium hexachloroiridate is sodium hexachloroiridate (III) and its hydrate.
7. The method for preparing an In2O3-based wrench-shaped photocatalyst according to claim 1, characterized in that: In step 5, the deposition reduction reaction is carried out for 2 hours, and the amount of deposition is 0.3-0.7 wt%.
8. The method for preparing an In2O3-based wrench-shaped photocatalyst according to claim 7, characterized in that: The amount deposited was 0.5 wt%.
9. The method for preparing an In2O3-based wrench-shaped photocatalyst according to claim 1, characterized in that: The indium source is indium nitrate.
10. Use of an In2O3-based finger-shaped photocatalyst prepared by the method for preparing an In2O3-based finger-shaped photocatalyst according to any one of claims 1 to 9 in a photocatalytic γ-lactam reaction, characterized in that: The amount of photocatalyst added is 0.05-0.1 mol%.